Nghị quyết Miễn nhiệm chức vụ Ủy viên Ủy ban Thường vụ Quốc hội khóa XIV (Nghị quyết số: 145/2021/QH14) - Quốc hội (2021)
Toàn văn Nghị quyết Miễn nhiệm chức vụ Ủy viên Ủy ban Thường vụ Quốc hội khóa XIV (Nghị quyết số: 145/2021/QH14)